2020
DOI: 10.3390/plants9030336
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Identification and Expression Profile Analysis of the NF-Y Transcription Factor Gene Family in Petunia hybrida

Abstract: Nuclear Factor Ys (NF-Ys) are a class of heterotrimeric transcription factors that play key roles in many biological processes, such as abiotic stress responses, flowering time, and root development. The petunia (Petunia hybrida) is a model ornamental plant, and its draft genome has been published. However, no details regarding the NF-Y gene family in petunias are available. Here, 27 NF-Y members from the petunia genome were identified, including 10 PhNF-YAs, 13 PhNF-YBs, and 4 PhNF-YCs. Multiple alignments sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Some NF-YC family genes have been shown to regulate flowering time through photoperiod-dependent pathway in Arabidopsis , rice, and tobacco [ 3 , 4 , 5 , 16 , 28 ]. In petunia, there are 27 members of the NF-Y family, including 10 PhNF-YAs, 13 PhNF-YBs, and 4 PhNF-YCs [ 43 ]. Until now, there were no reports on the functions of PhNF-YCs.…”
Section: Discussionmentioning
confidence: 99%
“…Some NF-YC family genes have been shown to regulate flowering time through photoperiod-dependent pathway in Arabidopsis , rice, and tobacco [ 3 , 4 , 5 , 16 , 28 ]. In petunia, there are 27 members of the NF-Y family, including 10 PhNF-YAs, 13 PhNF-YBs, and 4 PhNF-YCs [ 43 ]. Until now, there were no reports on the functions of PhNF-YCs.…”
Section: Discussionmentioning
confidence: 99%
“…On the whole, CmNF-YC members were more involved ( Figure 8 ), which was different from that in Petunia hybrida . PhNF-YAs were mainly involved in cold tolerance response [ 27 ]. In addition, CmNF-YB4/B7 was only up-regulated after 6 h of cold treatment, which might play a role in the early cold response.…”
Section: Discussionmentioning
confidence: 99%
“…AtNF-YA1 [ 22 ], OsNF-YC13 [ 23 ], and HvNF-YA1/A6 [ 24 ] are associated with plant salt tolerance. Recently, with the publication of the genome, a large number of NF-Y genes were found to be induced by cold, heat, salt, drought, or other stresses in various plants, such as grape [ 25 ], tea plant [ 26 ], petunia [ 27 ], cucumber [ 6 ], and poplar [ 28 ]. Although extensive studies of the NF-Y gene family have been identified and functionally annotated in other plant species, little is known in melon.…”
Section: Introductionmentioning
confidence: 99%
“…NF-Y is a heterotrimeric transcription factor that includes three subunits: NF-YA, NF-YB, and NF-YC, and is conserved in nearly all eukaryotes. In the past two decades, many genes encoding NF-YC proteins have been identified in several species, including 20 NF-YC genes in Solanum lycopersicum [ 27 ], 15 NF-YC genes in Glycine max [ 28 ], 14 NF-YC genes Triticum aestivum [ 29 ], 14 NF-YC genes in Sorghum bicolor (L.) Moench [ 30 ], 14 NF-YC genes in Populus tomentosa [ 31 ], 13 NF-YC genes Arabidopsis thaliana [ 32 ], 13 NF-YC genes in Setaria italica [ 33 ], 12 NF-YC genes in Brachypodium distachyon [ 34 ], 12 NF-YC genes in Physcomitrella patens [ 35 ], 10 NF-YC genes in Malus Domestica [ 36 ], 9 NF-YC genes in Arachis Hypogaea L. [ 37 ], 9 NF-YC genes in Vitis vinifera [ 38 ], 7 NF-YC genes in Phaseolus vulgaris [ 39 ], 7 NF-YC genes in Z. jujube [ 40 ], 7 NF-YC genes in Oryza sativa [ 41 ], 6 NF-YC genes in Prunus persica [ 42 ], 5 NF-YC genes in Citrus [ 43 ], 4 NF-YC genes in Citrullus lanatus [ 44 ], 4 NF-YC genes in Petunia hybrida [ 45 ], and 3 NF-YC genes in Brassica napus [ 46 ]. In this study, five NF-YC coding genes were obtained by PCR amplification in wild chrysanthemums, which was less than that reported in most plants.…”
Section: Discussionmentioning
confidence: 99%